Analysis of the Effectiveness of Social Assistance Distribution for the Poor Family (Case Study in Sikayu Village, Comal, Pemalang, Central Java) - Sheila Arisonya Mulyani; Hendri Hermawan Adi Nugraha; Zohaib Hassan Sain (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
Governmental support programs aimed at enhancing people's economic well-being are essential components of their initiatives. These initiatives are crucial in fostering more prosperous livelihoods for individuals. Nonetheless, issues often arise in the equitable distribution of such aid, primarily due to inaccuracies in identifying eligible recipients. Sikayu Village, located in Comal Subdistrict, Pemalang, is no exception, facing similar challenges in ensuring efficient allocation. That is the main aim of this research which is to examining the problem of social assistance in sikayu village. This study adopts a descriptive qualitative approach, employing a case study methodology, incorporating interviews and observations. Sikayu Village encounters various obstacles hindering the attainment of optimal effectiveness, particularly evident in deficient coordination among government bodies responsible for aid distribution and a flawed data management system for beneficiaries. Consequently, there is an imperative need to enhance the management of beneficiary data, bolster community engagement, and, notably, improve interagency coordination to address these shortcomings effectively.